The link between ischaemic stroke, ischaemic heart disease, and atrial fibrillation - El-Battrawy, Ibrahim; Hamdani, Nazha; Akın, Ibrahim (Europace, 2023)
The article by Ntaios et al.1 published in Europace describing the interaction among atrial fibrillation type, myocardial infarction, and mortality raised a huge interest among our research group. Authors showed that patients with first-diagnosed paroxysmal atrial fibrillation had higher risk of acute myocardial infarction compared with patients with non-paroxysmal fibrillation, attributed to the higher risk of non-ST-segment elevation myocardial infarction (nSTEMI) among patients with first-diagnosed paroxysmal atrial fibrillation. The rates of mortality and ischaemic stroke were similar regardless of the type of atrial fibrillation.
Veröffentlicht: 23. August 2023
Gesehen am 26.10.2023